First-in-human study of CPL’116 – a dual JAK/ROCK inhibitor – in healthy subjects - Rudzki, Piotr J.; Jarus-Dziedzic, Katarzyna; Włodarczyk, Dorota; Kaza, Michał; Pankiewicz, Piotr; Gierczak-Pachulska, Agnieszka; Banach, Martyna; Zygmunt, Beata; Piwowarczyk, Cezary; Żero, Paweł; Rabczenko, Daniel; Segiet-Święcicka, Agnieszka; et al. (Frontiers in Pharmacology, 2025)
BackgroundCPL’116 is a novel Janus kinase (JAK) and Rho-associated coiled-coil containing protein kinase (ROCK) dual inhibitor and a promising drug candidate for the treatment of inflammatory and fibrotic diseases. We conducted this first-in-human, Phase I clinical trial to evaluate the safety, pharmacokinetics (PK), and exploratory pharmacodynamics (PD) of CPL’116 in healthy subjects.MethodsPhase I clinical trial in healthy White volunteers was conducted after single (n = 21, 10–300 mg) and multiple (n = 32, 30–240 mg or placebo, 14-day b.i.d.) administrations of CPL’116 including a food effect study (n = 12, 120 mg). The multiple ascending dose part was double-blinded and placebo-controlled. The primary endpoint was safety evaluation, and the secondary endpoint was PK. Exploratory PD was studied by measuring the inhibition of JAK and ROCK in the blood by assessing STAT1, STAT5, and MLC phosphorylation.ResultsSafety parameters were comparable between the placebo and active treatment groups, with no clinically meaningful variations in the safety parameters between the cohorts. No deaths or serious adverse events (SAEs) were reported. No influence on hematological parameters (neutrophil count, red cell distribution width, and mean corpuscular volume) was observed. Plasma Cmax and AUC increased proportionally in the dosing range of 60–240 mg. Median tmax ranged 2–3 h. Food increased the absorption of CPL’116. Compared to placebo, CPL’116 at 240 mg dose showed a decrease in the phosphorylation of STAT1 (Days 1 and 14, p < 0.05) and STAT5 (Day 14, p < 0.05). A decrease in MLC phosphorylation indicated a potential trend at p < 0.1.ConclusionCPL’116 was safe and well-tolerated by healthy subjects. The PK profile is well suited for twice-daily administration and justifies further clinical development. Exploratory PD studies indicated the ability of CPL’116 to affect the JAK and ROCK pathways in humans, hinting at its potential therapeutic role in diseases benefiting from its dual mode of action. The positive results of this study indicate the possibility of developing a novel class of therapeutics that address both inflammatory and fibrotic processes.Clinical Trial RegistrationMethodsclinicaltrials.gov, identifier NCT04670757.